Highly active antiretroviral therapy for critically ill HIV patients: A systematic review and meta-analysis. - Hugo Boechat Andrade; Cassia Righy Shinotsuka; Ivan Rocha Ferreira da Silva; Camila Sunaitis Donini; Ho Yeh Li; Frederico Bruzzi de Carvalho; Pedro Emmanuel Alvarenga Americano do Brasil; Fernando Augusto Bozza; Andre Miguel Japiassu (PLoS ONE, 2017)
Introduction It is unclear whether the treatment of an HIV infection with highly active antiretroviral therapy (HAART) affects intensive care unit (ICU) outcomes. In this paper, we report the results of a systematic review and meta-analysis performed to summarize the effects of HAART on the prognosis of critically ill HIV positive patients. Materials and methods A bibliographic search was performed in 3 databases (PubMed, Web of Science and Scopus) to identify articles that investigated the use of HAART during ICU admissions for short- and long-term mortality or survival. Eligible articles were selected in a staged process and were independently assessed by two investigators. The methodological quality of the selected articles was evaluated using the Methodological Index for Non-Randomized Studies (MINORS) tool. Results Twelve articles met the systematic review inclusion criteria and examined short-term mortality. Six of them also examined long-term mortality (≥90 days) after ICU discharge. The short-term mortality meta-analysis showed a significant beneficial effect of initiating or maintaining HAART during the ICU stay (random effects odds ratio 0.53, p = 0.02). The data analysis of long-term outcomes also suggested a reduced mortality when HAART was used, but the effect of HAART on long-term mortality of HIV positive critically ill patients remains uncertain. Conclusions This meta-analysis suggests improved survival rates for HIV positive patients who were treated with HAART during their ICU admission.